VULNERABILITY TO DROUGHTS AND DETERMINANTS OF DIVERSIFICATION OF TEMPORARY CROPS IN NORTHEAST BRAZIL: A QUANTILE REGRESSION ANALYSIS - Sá, Álvaro Robério de Souza; Gomes, Luziane da Silva (Revista Econômica do Nordeste, 2025)
This paper estimates the impacts of drought and identifies the determinants of diversification of temporary crops in the municipalities of Northeast Brazil. Using a quantile regression model with a fixed effects estimator, we find that diversification in rainfed agriculture increases with climate variability (climate change) but decreases with droughts. However, the impacts of droughts are smaller in areas with greater agricultural diversification. We also identify that family labor, conservation of natural resources, non-agricultural income, local market size, rainfall, access to rural credit, and subsistence farming are directly related to agricultural diversification, while mechanization, land use, temperature, dam construction, and business farming are inversely related. Taken together, these results support the recommendation of agricultural diversification policies to promote economic resilience, agrarian sustainability, and the adaptation of local farmers to climate change.